Round of Searching assignment, EPD 151 Spring 2010 - Kindschi, Amy; Wheeler, Diana; Vellardita, Lia (My University, 2010)
Round of Searching assignment used in EPD 151, Spring 2010.
Keywords: critical thinking; search analysis; database search process; research process; EPD; EPD 151